The Use of Narrative Tradition in Haidar Haidar's Stories - Eid Hassan Mahmoud; Fairouz Abbass (دراسات فی اللغه العربیه و آدابها, 2014)
The narrative tradition has an important place in Haidar Haidar's fictional strategies as he has paid especial attention to employing these strategies in styleØ conversationsØ and topics togetherØ and he has sought to produce new meanings through using narrative techniques (the story-tellerØ narrationØ the logic of the story) in the present time and interpreting each of them in the light of the others in a unique anecdotal language that shows the substantive essence of this heritage and redrafts it in a creative artistic way which goes along with the pillars of fiction and its modern principles. The narrator is able to employ this tradition to tie the past and the present together. He has written wrote about a vision in the past which correspond with the realities of his society. He has also established a narrative style which relies on the tradition and matches with it without recopying it. This has led to a new narration that presents a grim image of society which has inherited injustice from the past and has added more injustice to it. The author expresses the crises of his characters in their respective communities in the past and present.